“JENTON TURUN JENTON” LEADERSHIP OF TUMENGGUNG NGGRIP ON COMMUNITY ORANG RIMBA IN KEDUNDUNG MUDA, BUKIT DUABELAS NATIONAL PARK, JAMBI, INDONESIA - Sipin Putra (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2019)
This study aims to describe Tumenggung Nggrip on Community Orang Rimba in Bukit Duabelas National Park. Political leadership can be analyzed from the Tumenggung Nggrip kinship system in this community. Custom rules “Jenton Turun Jenton” justify the political leadership in community-based on lineage by the previous leader. Politically Tumenggung Nggrip is the benefit of having a father who was to be Tumenggung. Tumenggung required to have some expertise prominent than the other. Ability to lead and understanding of custom that has been passed on by parents. Tumenggung Nggrip is superior compared with other individuals. Leadership held by close relatives of the Tumenggung. The kinship system in political leadership is able to confirm the position of Tumenggung as a respected. It has the power of access to economic resources, social and relationship with outsiders. Political level as a community can be analyzed as a form of democracy, but in practice, it tends to be influenced by the attitude of a leader in custom enforcement. Social system and political organization Orang Rimba is built on the concept of family, marriage, and kinship system.